Citronella Farm Business Partnership Strategy - Irene Kartika Eka Wijayanti,; Zulkifli, Lutfi; Tatang Widjojoko,; Alpha Nadeira Mandamdari,; Rifki Andi Novia,; Sunendar,; Syahrul Ganda, (JURNAL AGRIBISAINS, 2024)
The objective of this study is to provide a new strategy for establishing a business partnership in citronella cultivation in Kedungrandu Village, Patikraja District, Banyumas Regency, Central Java, Indonesia. The study methodology uses SWOT analysis for identifying both internal and external factor. The internal factors comprise four strengths and three weaknesses. The external factors encompass four opportunities and two potential threats. The use of SWOT analysis factors provides eight strategies, which will be evaluated using the AHP analysis instrument to determine the strategic priorities for the citronella farming business partnership in Patikraja District.